2010
DOI: 10.1007/s00216-010-4302-7
|View full text |Cite
|
Sign up to set email alerts
|

Droplet microfluidics with magnetic beads: a new tool to investigate drug–protein interactions

Abstract: In this study, we give the proof of concept for a method to determine binding constants of compounds in solution. By implementing a technique based on magnetic beads with a microfluidic device for segmented flow generation, we demonstrate, for individual droplets, fast, robust and complete separation of the magnetic beads. The beads are used as a carrier for one binding partner and hence, any bound molecule is separated likewise, while the segmentation into small microdroplets ensures fast mixing, and opens fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 40 publications
0
76
0
Order By: Relevance
“…It is basically the technology that permits the manipulation of small volumes of fluids inside microchannels and has uncovered applications in numerous fields, such as biology, physics [1,2], biotechnology and pharmacy. It offers the potential to utilize tiny quantities of samples as well as reagents to detect, separate and synthesize materials with high sensitivity and resolution, or to make use of the flow patterns that occur inside microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…It is basically the technology that permits the manipulation of small volumes of fluids inside microchannels and has uncovered applications in numerous fields, such as biology, physics [1,2], biotechnology and pharmacy. It offers the potential to utilize tiny quantities of samples as well as reagents to detect, separate and synthesize materials with high sensitivity and resolution, or to make use of the flow patterns that occur inside microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…The current chip is designed for sample introduction only. However, with slight changes of the design advanced introduction and sample preparation steps cloud be implemented on-chip, e.g., dilution [27][28][29] , ultra fast mixing 30 , chemical reactions 31 , separation [32][33][34] , or cell sorting 35,36 . Under advanced introduction devices we understand for example the introduction of sample and standard droplets sequentially or parallel with a single chip.…”
Section: Discussionmentioning
confidence: 99%
“…Many microfluidic devices have been designed for ligand-binding studies to investigate the interaction of drugs with specific targets 43,44 . A recent study using droplet microfluidics demonstrated the interaction of human serum albumin (HSA) and an anti-coagulant drug warfarin using droplet microfluidics 45 . In this study, magnetic beads were coated with HSA in a solution following which 14 C-labelled warfarin was added and allowed to reach equilibrium.…”
Section: Drug Discoverymentioning
confidence: 99%